Portable, stable, and sensitive assay to detect phosphate in water with gold nanoparticles (AuNPs) and dextran tablet. Issue 11 (7th May 2021) - Esfahani, AmirReza R.; Sadiq, Zubi; Oyewunmi, Oyejide Damilola; Safiabadi Tali, Seyed Hamid; Usen, Ndifreke; Boffito, Daria Camilla; Jahanshahi-Anbuhi, Sana
Abstract : A novel and highly sensitive tablet-based colorimetric sensor is developed for the detection of phosphate (Pi) in drinking and surface water using mercaptoacetic acid-capped gold nanoparticles (MA-AuNPs). Abstract : A novel and highly sensitive tablet-based colorimetric sensor is developed for the detection of phosphate (Pi) in drinking and surface water using mercaptoacetic acid-capped gold nanoparticles (MA-AuNPs). Characterization of AuNPs and MA-AuNPs was achieved by ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM) and Dynamic light scattering (DLS). The principle of this sensor is based on the aggregation and disaggregation mechanisms of AuNPs that result in a color change from blue to red due to the surface plasmon resonance effect, where europium ions (Eu 3+ ) act as the aggregating agent. Herein, dextran is used to encapsulate the Eu 3+ ions into a tablet format to make the detection system user friendly. Hence, the sensor only requires dissolving a Eu 3+ -dextran tablet into the water sample and subsequently adding MA-AuNPs for the colorimetric quantification of phosphate. This assay is very sensitive with a calculated detection limit of 0.3 μg L −1 and an upper detection limit of 26 μg L −1, while 10 μg L −1 is the allowable limit of Pi in drinking water. A comparative study with a conventional Hach kit confirmed the accuracy of our sensor. Also, real water samples from river, lake, and tap sources were tested to examine the sensor's applicability towards commercialization. The assay did not interfere with common ions in water, thus being Pi-specific, and the performance of the assay was stable for up to at least three weeks. Overall, our new approach provides a simple, stable, rapid, low-cost and promising device for Pi detection in water.